Profile and spatial distribution on maternal mortality - Carla Alaíde Machado Ruas; Joice Fernanda Costa Quadros; Jucimere Fagundes Durães Rocha; Fernanda Cardoso Rocha; Gregório Ribeiro de Andrade Neto; Álvaro Parrela Piris; Bruna Roberta Meira Rios; Sabrina Gonçalves Silva Pereira; Claudia Danyella Alves Leão Ribeiro; Giselle Mara Mendes Silva Leão (Instituto Materno Infantil de Pernambuco, 2020)
Abstract Objectives: to describe profile and spatial distribution on maternal mortality in a city in the North of Minas Gerais-Brazil. Methods: a descriptive, cross-sectional, documentary and quantitative study was carried out in 31 (100%) Fichas de Investigação de Óbito Materno do Comitê de Mortalidade Materna (Maternal Mortality Investigation Data Forms from the Maternal Mortality Committee) from 2009 to 2013. Results: prevalence is observed in women between 20 and 34 years old, mixed race, single and with low schooling. Of the deaths classified, 48.2% are direct obstetric death and 74.2% would be likely avoidable. The most prevalent causes of death were pregnancy-specific hypertensive disease; circulatory system disease; neoplasms; coagulopathies and post-abortion infection. In relation to prenatal care, only 20 women performed it, and most performed less than six prenatal consultations and in relation to the end of gestation, 68.1% underwent cesarean childbirth. Regarding to the descriptive spatial analysis, we identified a higher occurrence of maternal deaths in the areas of medium and high social vulnerability. Conclusions: maternal mortality is a strong indicator of women's healthcare, there is a necessity to readjust women's healthcare in the puerperal pregnancy cycle. New healthcare practices for women are needed, due to the referred bond and responsible care.